ISOLATION AND IDENTIFICATION OF ANTIMICROBIAL PROTEINS FROM THE LEAVES OF VALERIANA HARDWICKII AND SENNA OBTUSIFOLIA - Harsha N, Madhuri; Dulloo, Piyushika; Dulloo, Piyushika; S, Rupachandra; S, Rupachandra; S, Jagadeeshwari; S, Jagadeeshwari; Davina M, Joann; Davina M, Joann; S, Porkodi; S, Porkodi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective : The aim of this study was to screen the antimicrobial activity of trypsin-digested peptides isolated from the protein extracts of Valeriana hardwickii and Senna obtusifolia. Methods: The proteins were extracted from the leaves of V. hardwickii and S. obtusifolia which were analyzed using sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The protein extracts were digested using trypsin which was identified using reverse-phase high-performance liquid chromatography analysis. Further, the antimicrobial efficacy of the digested peptides was investigated. Result: Peptide extracts of V. hardwickii exhibited potent antifungal and antibacterial activity at the maximum concentration of 1.5 mg/ml. Similarly, S. obtusifolia exhibited increased antifungal and antibacterial activity at the concentration of 1.44 mg/ml. Conclusion: The trypsinized extracts of V. hardwickii and S. obtusifolia were plated against Bacillus subtilis which is a promising antibacterial agent.